Stop, Talk & Learn: socialization in a university open space - Asher, Amy Lynn (Kansas State University, 2006)
Landscape architects have the opportunity to compose a setting in which certain types of socialization may prosper by altering the environment to improve opportunities for socialization. Socialization, or interpersonal contact, is a primary determinant in the formation of individual characteristics and behavior. The experiences to which one is exposed contribute to personal development and are affected by environmental stimuli. The purpose of this thesis is to document the design process of a project that has enhancement of socialization as the primary goal. This study includes a review of the existing literature to determine the design elements that can improve socialization in the designed environment employing the theories of Randolph Hester (1975), Clare Cooper Marcus with Trudy Wischemann (1998) and William “Holly” Whyte (1980). These design elements are categorized by the types of socialization that they can facilitate: manifest, latent, and spontaneous interaction. Next, a case study of Spaights Plaza on the University of Wisconsin-Milwaukee campus was conducted to define the current socialization levels among university users. A new design addressing socialization elements was drafted, and a comparative analysis of the existing and proposed designs concludes the thesis.
Keywords: Socialization design; Campus design; University of Wisconsin Milwaukee; Landscape Architecture (0390)